Synthesis and Optical Properties of BODIPY with Active Group on meso- Position - Matvey, Gruzdev; Ulyana, Chervonova; Natalia, Bumagina; Arkadiy, Kolker (Letters in Organic Chemistry, 2016)
Background: In this work a few approaches for the synthesis of 4,4-difluoro-8-(4’- carboxyphenyl)-4-bora-3a,4a-diaza-s-indacene are considered. The process of obtaining this boron fluoride complex involves the following stages: introduction of the protective group (methoxy-, 1’- pyrrolidine-2,5-dion-, trichloroethoxy-) on the carboxy-group of 4-formylbenzoic acid, condensation with pyrrole, removal of protection, oxidation, and complexation proper. A method of direct condensation of pyrrole with the 4-formylbenzoic acid in the presence of a catalytic amount of 0.1 M HCl was proposed to achieve a high yield of the target product. All synthesized compounds were characterized by infrared spectroscopy, nuclear magnetic resonance spectroscopy, mass spectrometry and elemental analysis. Values of fluorescence quantum yield and Stokes shift were calculated for boron fluoride complexes of dipyrrolylmethenes. Methods: IR spectra were recorded on a Bruker Vertex 80V device in the regions of 7500–350 cm–1 from pellets with KBr. The NMR spectral studies on the nuclei 1Ц#157; and 13С were performed on a Bruker Avance-500 instrument (500.13 MHz) in CDCl3, the internal standard was TMS. Elemental analyses of crystalline compounds were carried out on a FlashEA 1112 analyzer. Mass spectra were registered on a JMS-700 JEOL (FAB) and JMS-100GCV JEOL (EI) mass-spectrometers. UV/V is spectra and fluorescence spectra were recorded on a spectrofluorimeter СЦ#156; 2203 (SOLAR) in CH2Cl2, with square quartz cavity being 10 mm thick. The fluorescence quantum yield was determined by formula utilizing fluorescein in 0.1 M NaOH as a standard (S=0.85). Results: All the synthesized compounds have a smaller fluorescence quantum yield as compared to the standard and most BODIPY, in which the meso-position does not contain aryl and the other mobile substituents. The decrease in the quantum yield of meso-aryl-substituted BODIPY due to the rotation of the meso-substituent relative BODIPY core leads to non-radiative transitions. Fluorophores are stable upon illumination (no changes in the electronic absorption and fluorescence spectra are observed when they are affected by a continuous light). The Stokes shift is from 30 to 52 nm. Conclusion: A few approaches to synthesize 4,4-difluoro-8-(4’-carboxyphenyl)-4-bora-3a,4a-diaza-sindacene are considered. The process of obtaining this boron fluoride complex involves the following stages: introduction of the protective group (methoxy-, 1’-pyrrolidine-2,5-dion-, trichloroethoxy-) on the carboxy-group of 4-formylbenzoic acid, condensation with pyrrole, removal of protection, oxidation, and complexation proper. A method of direct condensation of pyrrole with the 4-formylbenzoic acid in the presence of a catalytic amount of 0.1 M HCl was proposed to achieve a high yield of the target product. Values of fluorescence quantum yield and Stokes shift were calculated for boron fluoride complexes of dipyrrolylmethenes.
Keywords: Stokes shift